The role of admiral john lie in an effort to maintain and fill the independence of Indonesia in 1946 – 1967 - Ria Noviandani; Kayan Swastika; Sri Handayani (JURNAL HISTORICA, 2017)
This research aims at understanding the role of Admiral John Lie. It utilizes historical methods in analyzing data and facts. Three steps of research are applied in this writing. At an early stage the researcher collects data from books and. In the latter stage, various facts and findings are arranged one to another in order to discover the milestone of his contribution during the independence era. Thereafter in the final stage the researcher compiles stories and historical facts in a chronological manner. At least three important landmarks of his career could be traced back to understand his role in independence era: firstly the life before he joined the navy; secondly his role in the fight against the colonial rule; and thirdly his role in the military after the independence. We can conclude that John Lie had been grown up in the maritime community that which very positive for his career in the navy. In 1947 he made a heroic effort to penetrate the Dutch naval blockade in Singapore and smuggle rubber in exchange of weapons. Besides that, he made another important contribution to the nation when he led his troops in the fight against the rebellions of RMS and PRRI/Permesta. Keywords: John Lie, Maintaining independence, filling independence